Influence of features of agrotechnics on the productivity and quality of grain of different sorts of buckwheat in the conditions of Right-bank Foreststeppe of Ukraine - Полторецький, C. П. (Scientific Progress & Innovations, 2012)
The results of two-year researches of growing buckwheat varieties Elena and Amazon indicate that wide-row sowing with 30 cm row spacing is the most appropriate method of sowing under conditions of unstable moistening of southern part of Right-bank Forest-steppe. The application of this method in combination with seeding rate of 3 million germinable seeds per hectare made it possible to form an optimal leaf area for both varieties and get a considerably higher yield.